Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1997
DOI: 10.1115/97-gt-401
|View full text |Cite
|
Sign up to set email alerts
|

Inner Workings of Aerodynamic Sweep

Abstract: The recent trend in using aerodynamic sweep to improve the performance of transonic blading has been one of the more significant technological evolutions for compression components in turbomachinery. This paper reports on the experimental and analytical assessment of the pay-off derived from both aft and forward sweep technology with respect to aerodynamic performance and stability. The single stage experimental investigation includes two aft-swept rotors with varying degree and type of aerodynamic sweep and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 14 publications
2
52
1
Order By: Relevance
“…They found that forward sweep produced better results than backward sweep despite the fact that the flow was expected to be less swept relative to the shock wave. In fact [5] finds that the efficiency of conventional, back swept and forward swept fans was very similar with the main differences being that the forward swept fan had better stall margin and the back swept one worse stall margin than the conventional fan. Wadia et al also investigated a fan with tangential lean which can be regarded as another means of introducing sweep, the performance of this was not significantly different to that with backsweep.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…They found that forward sweep produced better results than backward sweep despite the fact that the flow was expected to be less swept relative to the shock wave. In fact [5] finds that the efficiency of conventional, back swept and forward swept fans was very similar with the main differences being that the forward swept fan had better stall margin and the back swept one worse stall margin than the conventional fan. Wadia et al also investigated a fan with tangential lean which can be regarded as another means of introducing sweep, the performance of this was not significantly different to that with backsweep.…”
mentioning
confidence: 72%
“…Some success has been claimed for this approach but little has been published. The most detailed results are given by Wadia et al [5], who used a combination of experiment and CFD to investigate the effects of sweep and lean on a highly loaded military fan. They found that forward sweep produced better results than backward sweep despite the fact that the flow was expected to be less swept relative to the shock wave.…”
mentioning
confidence: 99%
“…Through the single stage experiments, Wadia et al [3] concluded that forward sweep can result in improvements in both efficiency and stall margin, a unique combination. Forward swept rotor achieved about 1.5% higher mass flow rate at the design speed.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand forward sweep while retaining the stage efficiency significantly increases the high-speed stall margin. Backward swept blades exhibit thickening of the blade boundary layer behind the diffused portion of the shock front causing reduced performance near the casing (Wadia et al [4]). In related investigations, Gallimore et al [9,10] reported separation near the hub with backward swept blades.…”
Section: Introductionmentioning
confidence: 99%
“…Sweep is one of the methods proposed to alleviate the above problem. Since the blades are no longer radial, the radial shifting of the blade boundary layer will not result in accumulation of low energy fluid [2], Neubert et al [3], Wadia et al [4], Passrucker et al [5] have reported increased performance with forward swept blades. Forward sweep redistributes the flow reducing the secondary flow loss, in addition to reducing the tip loading in terms of the static pressure coefficient, (Bergner et al [6], Xu and Chen [7], Amano and Xu [8]).…”
Section: Introductionmentioning
confidence: 99%